(untitled) (Research, Society and Development, 2021)
In criminal lawsuits, the magistrate often needs technical contribution of an expert on the subject related to the crime, for the application of the penal sanction. This study aimed to analyze lawsuits, expert reports and epidemiological data of violent death cases, in which there was involvement of the face, head and neck in the region that covered by the Legal Medical Institute (LMI) of Araraquara-SP. For this purpose, decisions of the Court of Justice of São Paulo State were researched, in the period from 2012 to September 2017. The judgments were read and those related to consummated homicide, body injury followed by death and robbery were selected. The expert reports corresponding to the selected cases were searched in the LMI of Araraquara. This search resulted in 49 reports, which were analyzed. We observed that the majority of homicide and robbery victims were male, white, under 40 years of age and of low education level. The epidemiological data found were consistent with the data presented by Brazilian government agencies. The expert reports analyzed were performed exclusively by medical examiners, using technical language and detailed description of the lesions and the instruments that caused them. The most frequent causes of death were traumatic brain injury (41.67%), multiple trauma (10.42%), hemorrhagic shock (10.42%) and anemia (10.42%). The most frequent instruments, which caused injuries, were the perforating-blunt (26.42%), the forceful (22.64%) and the perforating-cutting (20.75%). In general, the reports presented good quality, tending to be of great help for the clarification of criminal justice.